Prevalence and predictors of PTSD and low resilience symptoms among subscribers of the MoreGoodDays supportive text messaging program: A cross-sectional study - Belinda Agyapong; Reham Shalaby; Ejemai Eboreime; Katherine Hay; Rachal Pattison; Mark Korthuis; Vincent Israel Opoku Agyapong (PLoS ONE, 2026)
Background Post-traumatic stress disorder (PTSD) is not uncommon among adolescents and young adults, with increased incidence after experiencing a traumatic event. MoreGoodDays, a self-subscription daily supportive text messaging program, co-designed with young adults, was launched in Alberta to provide free mental health support for adolescents and young adults to mitigate symptoms of stress, anxiety, depression, and PTSD. Objectives This study aimed to determine the prevalence and predictors of probable PTSD and low resilience among subscribers of the MoreGoodDays supportive text messaging program. Methods A cross-sectional online study was conducted among MoreGoodDays subscribers using the PTSD Checklist Civilian (PCL-C) version and the Brief Resilience Scale (BRS) scales. Data were analyzed with SPSS version 25. Chi-squared tests and multivariate logistic regression analysis were applied to identify predictors. Results Of the 1,045, subscribers of MoreGoodDays program, 343 completed the survey. 45.7% of the respondents experience probable PTSD and 51.7% had low resilience. Receiving mental health counseling, desire for counseling, and high ACE scores were strong predictors of both outcomes. Participants who had received mental health counseling in the past year were 13.7 times more likely to experience PTSD symptoms (OR = 13.70; 95% CI: 1.23–142.86) and 15.15 times more likely to experience low resilience than those who did not (OR = 15.15; 95% CI: 1.46–166.67). Again, those who desired to receive mental health counseling were 20.8 times more likely to experience PTSD symptoms (OR = 20.76; 95% CI: 2.61–165.401) and 29.4 times more likely to experience low resilience than those who did not (OR = 29.42; 95% CI: 3.31–261.445). Finally, those with a score of four or more on the Adverse Childhood Experience Questionnaire were 6.2 times more likely to experience probable PTSD symptoms than participants with zero scores (OR = 6.24; 95% CI: 1.46–26.67). Conclusion Probable PTSD and low resilience are prevalent, particularly among the youth with high ACE scores and those seeking mental health counseling, highlighting the need for targeted mental health promotion strategies. Government agencies and policymakers in the educational field for instance should endeavor to promote mental well-being by integrating mental health education into school curricula to build awareness and resilience.